IMPLEMENTASI WEBSITE E-COMMERCE PENJUALAN HANDPHONE BERBASIS LARAVEL PADA TOKO I-KO - Habibi Umam; Zulfahmi Syahputra; Rio Septian Hardinata (Cattleya Darmaya Fortuna, 2026)
Advances in information and communication technology have brought about substantial changes in the trade sector, particularly through the shift from conventional commerce to electronic commerce (e-commerce). The increasing number of internet users has motivated entrepreneurs to implement digital platforms to improve operational efficiency and expand market reach. This research focuses on the development of a web-based e-commerce system for I-Ko Store, a mobile phone retailer, as a strategic step to address the growing demand for online shopping services. This system was created to systematically organize product orders and is equipped with key features such as an informative product catalog and an integrated digital payment system. The development process involved several stages, including requirements analysis, system design, coding using the PHP programming language, testing, and system maintenance. Functional testing was conducted using a black-box testing approach to verify that each feature worked according to predetermined specifications. The results demonstrated that the system functioned optimally and supported more efficient transaction management. The implementation of this e-commerce system is expected to increase customer satisfaction, optimize business activities, and strengthen I-Ko Store's competitiveness in the digital market.